Síntese de 1H-isocalcogenocromenos via reação de ciclização nucleofílica de benzodiinos promovidas por calcogenolatos de sódio - Maroneze, Adriano (2024)
In this study, we developed a synthesis for 1H-isocalcogenochromenes through a nucleophilic cyclization reaction of benzodiynes with selenide calcogenolates. We investigated the central parameters influencing this cyclization and established optimal reaction conditions applicable to various substrates to assess the method's scope. The results revealed that 1H-isoselenochromenes were produced in higher yields when reactions were performed by adding NaBH4 (3 equivalents) at 75 °C under a nitrogen atmosphere to a suspension of elemental selenium (2.0 equivalents) in dimethylformamide (2 mL). After one hour, a solution of benzodiynes (0.25 mmol) in ethanol (3 mL) was introduced at room temperature. The reaction was maintained at 75 °C until the starting material was fully consumed. These optimal conditions were applied to benzodiynes with substituted aromatic rings and alkyl groups directly linked to alkynes, resulting in the synthesis of sixteen new compounds with yields ranging from 52% to 82%. We also extended the methodology to 1H-isothiochromene derivatives, yielding two new examples with yields between 63% and 78%. However, attempts to apply this methodology to 1H-isotelurochromenes did not yield the desired compounds. The synthesized 1H-isocalcogenochromenes were readily transformed into three new classes of compounds using established methods. In one class, utilizing boronic acids in coupling reactions, six new products were obtained with yields ranging from 54% to 75%. Using selenium dioxide and potassium iodide in DMSO resulted in three additional compounds with yields of 52% to 66%. Finally, the application of an organolithium reagent yielded two vinyl selenide products with yields between 72% and 74%. To elucidate the reaction mechanism, we conducted several control experiments.